Effect of Camera Angle on Perception of Trust and Attractiveness. (January 2018) - Baranowski, Andreas Michael; Hecht, Heiko
Film theories have long proposed that the vertical camera angle influences how the scene and the character in it are interpreted. An elevated camera (high-angle shot) should diminish the qualities of the actor, whereas a lowered camera (low-angle shot) should elevate the actor in perspective as well as in the viewer's opinion. We were interested in how this holds up for the impression of trustworthiness and attractiveness that the spectator receives of the actor. We filmed 12 actors in a scenario inspired by a TV show called Split or Steal, which features a one-time version of the prisoner's dilemma. Subjects had to rate trustworthiness and attractiveness of the actors, and also judge if the actors would lie or tell the truth. We found that actors were rated as most trustworthy when filmed from eye-level, and less so when the camera was lowered or raised. Camera elevation had no effect on attractiveness. Also, personality ratings of the actors were not altered by varying camera angle. We conclude that context plays an important role in how camera angle interacts with actor perception.